Everyday Streets Inclusive approaches to understanding and designing streets - Martire, Agustina; Hausleitner, Birgit; Clossick, Jane (UCL Press, 2023)
Everyday streets are both the most used and most undervalued of cities' public spaces. They are places of social aggregation, bringing together those belonging to different classes, genders, ages, ethnicities and nationalities. They comprise not just the familiar outdoor spaces that we use to move and interact but also urban blocks, interiors, depths and hinterlands, which are integral to their nature and contribute to their vitality. Everyday streets are physically and socially shaped by the lives of the people and things that inhabit them through a reciprocal dance with multiple overlapping temporalities. The primary focus of this book is an inclusive approach to understanding and designing everyday streets. It offers an analysis of many aspects of everyday streets from cities around the globe. From the regular rectilinear urban blocks of Montreal to the military-regulated narrow alleyways of Naples, and from the resilient market streets of London to the crammed commercial streets of Chennai, the streets in this book were all conceived with a certain level of control. Everyday Streets is a palimpsest of methods, perspectives and recommendations that together provide a solid understanding of everyday streets, their degree of inclusiveness, and to what extent they could be more inclusive.